Chasing flavor : techniques and recipes to cook fearlessly - Kluger, Dan; Fauchald, Nick (Houghton Mifflin Harcourt, 2020)
"In his debut cookbook, James Beard Award-winning chef Dan Kluger shares 190 recipes to help home cooks master flavor and technique"--